The economics of free: freemium games, branding and the impatience economy - Evans, Elizabeth (Sage, 2015)
The gaming industry has seen dramatic change and expansion with the emergence of ‘casual’ games that promote shorter periods of game play. Free to download, but structured around micro-payments, these games raise the complex relationship between game design and commercial strategies. Although offering a free gameplay experience in line with open access philosophies, these games also create systems that offer control over the temporal dynamics of that experience to monetise player attention and inattention. This article will examine three ‘freemium’ games, Snoopy Street Fair, The Simpsons’ Tapped Out and Dragonvale, to explore how they combine established branding strategies with gameplay methods that monetise player impatience. In examining these games, this article will ultimately indicate the need for game studies to interrogate the intersection between commercial motivations and game design 2 and a broader need for media and cultural studies to consider the social, cultural, economic and political implications of impatience.